2014
DOI: 10.1177/1076029614533143
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Sulodexide in the Prevention of Postthrombotic Syndrome

Abstract: Sulodexide administration after DVT appears to be effective in preventing PTS in association with recommended management and a number of recurrent DVTs. Modalities of treatment, dosages, and timing of administration should be explored in more comprehensive and complete studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
(54 reference statements)
0
20
0
2
Order By: Relevance
“…Sulodexide comprises two fractions: a fastmoving heparin fraction (80%), which has affinity for antithrombin III, and a dermatan sulphate fraction (20%) that has affinity for heparin cofactor II [29]. In clinical trials it has demonstrated efficacy in the treatment/prevention of vascular diseases associated with increased thrombotic risk, including peripheral arterial occlusive diseases [30,31], post-myocardial infarction [32], recurrent deep vein thrombosis [33-35] and post-thrombotic syndrome [36,37].…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…Sulodexide comprises two fractions: a fastmoving heparin fraction (80%), which has affinity for antithrombin III, and a dermatan sulphate fraction (20%) that has affinity for heparin cofactor II [29]. In clinical trials it has demonstrated efficacy in the treatment/prevention of vascular diseases associated with increased thrombotic risk, including peripheral arterial occlusive diseases [30,31], post-myocardial infarction [32], recurrent deep vein thrombosis [33-35] and post-thrombotic syndrome [36,37].…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…However, Luzzie et al . evaluated the presence of post‐thrombotic syndrome in a registry of 339 patients after completion of anticoagulation for deep vein thrombosis (DVT) . Patients chose whichever treatment option they preferred: (i) standard management with compression, exercise, and risk factor reduction; (ii) sulodexide 25 mg twice daily plus standard therapy; or (iii) aspirin 100 mg daily plus standard therapy.…”
Section: Cvedmentioning
confidence: 99%
“…The utility of sulodexide in the prophylaxis of post-thrombotic syndrome was also evaluated based on a registry of 339 patients [24]. The incidence of the post-thrombotic syndrome after 60 months was lower in the group receiving sulodexide (12.2% vs. 19.5% in the standard treatment group and 12.2% vs. 23.5% in the aspirin group; P < 0.05 for both analyses).…”
Section: Administration Of Sulodexide In Chronic Venous Diseasementioning
confidence: 99%